Estimation of parameters for load-sharing parallel systems under exponential Pareto distribution. (April 2022) - Zhang, Zhengcheng; Yang, Yonghong; Li, Danqing
This article deals with the estimation of parameters for the load-sharing parallel system when the underlying distribution of component lifetime is exponential Pareto. The appropriate iterative method is used to get the parameter estimators. And the asymptotic distribution of the proposed maximum likelihood estimator is presented. For the model simplified, the maximum likelihood and best asymptotic unbiased estimators of parameters are obtained. Moreover, the confidence intervals for the parameters are constructed using the parameter bootstrap technique. In the end, some appropriate simulation methods and an example are used to substantiate the proposed methods.